2008
DOI: 10.1111/j.1540-8159.2007.00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Interatrial and Interventricular Electromechanical Delays from P/QRS Measurements: Value for Pacemaker Timing Optimization

Abstract: Inter-atrial and inter-ventricular electromechanical delays can be predicted from P-wave and QRS durations. These measurements allow AV delay optimization in DDD and cardiac resynchronization therapy devices with no need of Doppler echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
1
11
0
2
Order By: Relevance
“…In this study, the optimal AV delay was determined by identifying the AV interval with the narrowest QRS width in the BiV + intrinsic pacing group, which was performed by ECG but not echocardiography. Chirife, et al 21) showed that inter-atrial and inter-ventricular electromechanical delays can be determined by P-wave and QRS durations, indicating that AV delay optimization in CRT could be predicted by ECG with no need for echocardiography, which supported our study findings.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the optimal AV delay was determined by identifying the AV interval with the narrowest QRS width in the BiV + intrinsic pacing group, which was performed by ECG but not echocardiography. Chirife, et al 21) showed that inter-atrial and inter-ventricular electromechanical delays can be determined by P-wave and QRS durations, indicating that AV delay optimization in CRT could be predicted by ECG with no need for echocardiography, which supported our study findings.…”
Section: Discussionsupporting
confidence: 90%
“…The relation between P‐wave duration or interatrial conduction interval and optimal AV delay has been explained previously 25–27 . Optimal AV interval requires LV contraction to start soon after the completion of LA contraction.…”
Section: Discussionmentioning
confidence: 94%
“…A high degree of atrial pacing can compromise CRT response because of the difference in sensed and paced AV delays, and the effect on left-sided fi lling in AV resynchronization. When programming the sensed AV (SAV) and paced AV (PAV) delays, it is important to keep in mind that the PAV delay is usually longer than the SAV delay [ 16 ]. Latency in sensing and capture along with interatrial conduction delay contributes to this difference.…”
Section: Atrioventricular Optimizationmentioning
confidence: 99%